UI/UX Design of the Shop Feature on the Seafood by Aruna Website Using the Design Thinking Method - Anugerah Tirta Kenanga Unggul Mitra Mandiri; Rangga Gelar Guntara; Asep Nuryadin (TIERS Information Technology Journal, 2024)
The current Seafood by Aruna website functions solely as a landing page to promote products, with actual sales still conducted through a marketplace. This reliance on a marketplace limits the brand's control over personalization, customer value, shopping experience, and brand identity due to strict platform policies and standards. Additionally, shifts in consumer behavior in the digital era indicate a desire for a more personalized, sustainable shopping experience that meets specific needs, including accurate product information and quality assurance. To address these challenges, this research aims to design an online shopping feature for the Seafood by Aruna website using the Design Thinking method. This approach is applied to understand user needs and address various pain points faced by consumers when shopping for seafood online. The research found that users require accurate delivery, reliable product information, and assurances of product freshness. Testing of the designed features using the System Usability Scale (SUS) yielded an average score of 90.12, categorized as "Best Imaginable." This score reflects that the developed features meet user expectations, thanks to the effective application of the Design Thinking method. The implications of this research suggest that developing a dedicated e-commerce platform enables Aruna to better control all aspects of the shopping experience, enhance customer satisfaction and loyalty, and strengthen its position in the e-commerce market. However, further development is needed to adapt the features to changing consumer behavior and market trends.